Synergetic effect of Ce/Zr for ethanol synthesis from syngas over Rh-based catalyst. (15th February 2023) - Zhu, Caixia; Xu, Kaizhuang; Fang, Yuan; Lv, Qian; Jiang, Kun; Zhao, Huibo; Chen, Yang; Wang, Peng; Yang, Hua; Wu, Lizhi; Tang, Yu; Tan, Li
Graphical abstract: Highlights: The Rh δ+ active sites in Rh-based catalysts favored ethanol synthesis from syngas. A new carrier was designed by doping Ce into the ZrO2 lattice. The surface oxygen vacancies and the new carrier could stabilize and anchor the Rh δ+ active sites. Ce modified ZrO2 carrier suppressed the side products of CO2 . Abstract: The direct synthesis of ethanol from syngas is a promising way in the field of clean and efficient use of fossil fuel, but it still suffers from insufficient ethanol selectivity and understanding of active sites. In this work, the Rh-based catalyst with Ce as promoter and ZrO2 as carrier exhibits excellent catalytic performance, showing the selectivity of ethanol toward 24.3 %. Moreover, the yield of methane decreases to 4.8 %, and the formation of CO2 is inhibited to a certain degree by tuning the active sites. The carrier is changed by doping Ce into the ZrO2 lattice, which assists to form the Rh δ+ active sites. The synergetic effect of Ce and Zr is important to influence the state of Rh species in the catalysts, leading to the differences in the CO hydrogenation process. On the other hand, the Rh δ+ active sites are also stabilized by promoted surface oxygen vacancies in the 2.0Rh5.0Ce-ZrO2 catalyst. The high-activity catalyst with Rh δ+ active sites will be helpful to understand the real active sites of Rh-based catalysts for ethanol synthesis from syngas, thereby guiding further design of the related catalyst with high performance to meet the industrial demand in syngas converting to ethanol.